Enacting a public theology - Pearson, Clive (Sun Media, 2019)
The practice of a public theology is to identify issues that require attention for the sake of a civil society and the flourishing of all. In diverse ways the writers of Enacting a Public Theology recognise that the present is a volatile moment in time. The publication explores the loss of confidence in the contemporary expressions of democracy; the climate emergency accompanies the dawn of the Anthropocene; the migration of people raises concerns to do with identity, belonging and where is home; the invasion of land wrongly described as terra nullius and then invaded demands a deepened praxis of reconciliation between first and second peoples; and lastly there is an urgent need to speak into the situation of those pushed to the margins because of HIV/Aids--Back cover.